The Effect of Storytelling on Reducing Children's Fears in Nursing Procedures - Asih Fatriansari (CV. Get Press Indonesia, 2024)
The background of this study highlights that children often experience fear when undergoing nursing procedures in hospitals. Such fear not only becomes an obstacle in the implementation of medical actions but also worsens the overall experience of the child and may influence the success of the procedure. One widely used non-pharmacological approach to help reduce fear in children is storytelling, a narrative technique that provides emotional understanding and a calming effect. This study aimed to examine the effect of storytelling on reducing fear among children during nursing procedures. A quantitative design with a quasi-experimental approach was employed. The sample consisted of 30 children undergoing nursing procedures at Dr. Rasyidin Hospital Padang, divided into two groups: an experimental group that received a storytelling intervention and a control group without intervention. Children’s fear levels were assessed using a fear measurement scale before and after the procedure. Data were analyzed using a t-test to determine differences in fear levels between the two groups. The results showed a significant reduction in fear in the experimental group, with an average decrease of 4.5 points, compared to a 1.8-point decrease in the control group. Statistical analysis indicated a significant difference between the groups (p < 0.05). These findings suggest that storytelling is an effective non-pharmacological intervention for reducing children’s fear during nursing procedures. Therefore, storytelling can be integrated into routine nursing practice to enhance positive emotional responses, reduce anxiety, and support a more cooperative medical experience for pediatric patients.